Recovery beyond functional restoration: a systematic review of qualitative studies of the embodied experiences of people who have survived a stroke - Temmy Lee Ting Lo; Janet Lok Chun Lee; Rainbow Tin Hung Ho (BMJ Open)
Objective To synthesise the qualitative evidence of embodied experiences of people who have survived a stroke, the experiences of making sense of oneself, others and the world in the poststroke bodies.DesignQualitative systematic review.Data sources Five electronic databases, PsycINFO, PubMed, MEDLINE, CINAHL Plus and Cochrane Library, were employed to search for qualitative studies published up to February 2022.Inclusion criteria Literature in English that employed qualitative methods to investigate the embodied experiences of people who have survived a stroke.Quality appraisal Two reviewers independently appraised the quality of the included studies based on the tool developed by Salter et al in 2008. It consists of seven questions assessing the credibility and relevance of the studies. Discrepancies were resolved until a consensus was reached.Data extraction and synthesis Thematic synthesis was applied to synthesise the related findings from all the included studies. Two reviewers were involved in the process.Results 1482 records were identified. After the screening process, 34 studies were included in this review. Three analytical themes and their related descriptive themes emerged. Analytical themes included ‘disconnection between oneself, others and the world,’ ‘the transitional period: exploring and negotiating,’ and ‘reconnecting with oneself, others and the world’.Conclusion The findings demonstrated that the embodied experiences of people who have survived a stroke progressed from feeling disconnected to reconnecting with themselves, others and the world. Stroke recovery should not only be limited to functional restoration. Approaching ‘re-embodiment’, the realignment between oneself and one’s body, is crucial in reintegrating with others and the world on the trajectory toward recovery.PROSPERO registration number CRD42020183125